Competence of teachers graduates and education leaders in the 21st century - Helina Apriyani (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The competence of Teachers, Graduates and Leaders in the 21st century is very much needed. Superior competence and being able to compete in the era of globalization which demands human resources that have qualified quality and are able to keep up with the times. Currently, Indonesia as a developing country must be able to create superior human resources who are able to innovate and provide benefits to others. This study uses a qualitative approach and literature study methods in collecting data obtained from interviews, observation and searching for material from various literature from library books, modules and internet information media. Furthermore, increasing competence is carried out by increasing skills, education and skills. It takes maximum effort from within the individual himself for this improvement. The results of this study can be obtained information that competence is very important and must be owned by teachers as agents of change and provide learning transformation for students in an effort to improve the quality of learning outcomes. Furthermore, having superior abilities for graduates to be able to compete in the globalization era that demands qualified skills. As a future leader who will later make changes in improving education, the quality of teachers and the quality of graduates must have the competence of a superior future leader.